Hazardous waste site soil remediation theory and application of innovative technologies - Wilson, David J.; Clarke, Ann N. (Environmental science and pollution control series, 1994)
Introduces various techniques for soil remediation, including chemical fixation/stabilization, soil vapor extraction, thermally enhanced vapor stripping, biodegradation, and air sparging. This title describes the ex shu technique of thermal desorption of soil contaminants - a low-cost alternative to incineration for the removal of organics.